Rumination, experiential avoidance, and dysfunctional thinking in eating disorders. - Rawal, A; Park, R; Williams, J (2010)
The majority of research in eating disorders (ED) has investigated the content of disorder-specific thoughts, while few studies have addressed underlying cognitive-affective processes. A better understanding of processes underpinning ED may have important implications for treatment development. Two studies were conducted that investigated levels of rumination, beliefs about rumination, experiential avoidance, and aspects of schematic thinking in individuals with eating pathology. The latter was assessed with a newly designed ED-Sentence Completion Task (ED-SCT). Study 1 (N = 177) examined relations between ED psychopathology and these variables in a student population. Extending this, Study 2 (N = 26) assessed differences between patients with anorexia nervosa and healthy control participants. The results showed that ED psychopathology was related to disorder-specific cognitions, experiential avoidance as well as ruminative brooding but not reflection. A follow-up of anorexia nervosa patients indicated that changes in ED psychopathology were associated with changes in dysfunctional attitudes and maladaptive cognitive-affective processes. These findings highlight cognitive processes that may play an important role in the maintenance of eating pathology.